Uji Parameter Spesifik Ekstrak Etanol Umbi Sarang Semut Asal Kalimantan Tengah: Specific Parameter Testing of Ethanol Extract of Sarang Semut Tubers from Central Kalimantan - Rezqi Handayani; Fera Sartika; Eky Agus Setiawawan (JURNAL FARMASI DAN MAKANAN, 2025)
Standardization is a series of parameters, procedures, and measurement methods whose results constitute elements related to the pharmaceutical quality paradigm. The standardization stage begins with the preparation of sample extracts by establishing specific parameters. Based on chemical screening tests of Sarang Semut plants originating from Papua and Aceh, they contain phenolic and flavonoid compounds as antioxidants, while those from Central Kalimantan have antibacterial properties. The aim of this research is to identify and determine the pharmacognostic profile based on specific parameters of the ethanol extract of Sarang Semut tubers originating from Central Kalimantan. This research uses an experimental method with specific parameter procedures including extract identity, organoleptic examination, determination of water-soluble and ethanol-soluble compound content, and identification tests for secondary metabolite chemical compounds. The extraction of Sarang Semut tubers in this study used the Soxhlet extraction method. Based on the results of specific parameter tests, it is known that the ethanol extract of Sarang Semut tubers contains chemical compounds, namely alkaloids, flavonoids, saponins, tannins, steroids, triterpenoids, and quinones. The results of the water-soluble compound content test were 16.03%, and the ethanol-soluble compound content was 41.57%. The results obtained from this study can be concluded that the ethanol extract of Sarang Semut tubers has secondary metabolites with pharmacological effects, one of which is as an antibacterial agent, so it can be developed into a raw material for traditional medicine.